Effects of Coffee Form and Distributor Hole Angle on The Fluidization Behavior and Specific Energy Consumption in The Fluidized Bed Machine - Thatchapol Chungcharoen; Warunee Limmun; Sansanee Sansiribhan (Journal of Advanced Research in Fluid Mechanics and Thermal Sciences, 2021)
The fluidized bed technique was applied to use with the Robusta coffee in this research. fluidization behavior and specific energy consumption were investigated under various coffee forms and distributor hole angles. Moreover, the minimum fluidization velocity (Vmf) was also determined. Experiments are carried out in a sample bed height of 5 cm with ambience air. In this study, two coffee forms (Ripe coffee cherries; RCC and parchment coffee; PC) and three distributor hole angles (45º, 60º and 90º) are examined. The experimental result shown that the fluidization behavior is influenced by coffee form and distributor hole angle. The RCC and distributor hole angle of 60º provided the low pressure drop throughout the superficial air velocity. The low values of Vmf and SEC were also achieved in the RCC and distributor hole angle of 60º.
Keywords: Agricultural Engineering and Mechanization; Granular flow and fluidized beds; Belt Conveyor Systems Engineering